Main Approaches to School Inclusive Education - I. S. Samokhin; N. L. Sokolova; M. G. Sergeyeva (Научный диалог)
Two approaches to inclusive education are covered: systematic and axiological (valuable). The authors have positioned these approaches as the base, expressing doubts about the independent status of certain approaches, distinguished by modern researchers (command, conductive, individual). It is noted that the axiological approach focuses on the content of the new educational paradigm, while system approach - on its form. Also, the authors emphasize that the study allowed them to permanently ensure the interdisciplinary character of the phenomenon of inclusive education, its intersection with philosophy, cultural studies and other humanities. The relevance of the chosen topic is determined by the purpose of the implementation of the Federal law “On education in Russian Federation” in connection with which there is a need to study theoretical and practical components of “including” training and education. The novelty of the research is seen in the consideration of compassion as the basic value of Russian inclusive education (in contrast to the American tradition, the origins of which appear to be reasonable to seek in the democratic ideals, the cult of “diverse unity” (“E pluribus unum”)). Nevertheless, the authors come to the conclusion that another feeling must appear instead of compassion - respect. Teacher is advised to explain to the students that the disabilities of their peers forces them to serious and responsible work, which can be equated to a feat.